Pengaruh Faktor Budaya dan Faktor Sosial terhadap Keputusan Pembelian Sepeda Listrik di Desa Battal Situbondo - Desy Fitriati; Ahmad Hafas Rasyidi; Dassucik Dassucik (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to analyze the influence of cultural and social factors on electric bicycle purchasing decisions in Battal Village, Situbondo Regency. This study used a quantitative approach with a survey method. Primary data was collected by distributing questionnaires to electric bicycle consumers residing in Battal Village. The population in this study was all electric bicycle consumers, with a sample size of 50 respondents determined using a sampling technique appropriate to the research characteristics. The obtained data were then analyzed using multiple linear regression analysis to determine the influence of each independent variable on purchasing decisions. The results showed that cultural factors had a positive and significant influence on electric bicycle purchasing decisions. This indicates that community values, habits, and lifestyles also influence consumer decisions in choosing electric bicycles. Meanwhile, social factors did not have a significant influence on electric bicycle purchasing decisions. The adjusted coefficient of determination (Adjusted R Square) of 0.361 indicates that cultural and social factors explain 36.1% of the variation in purchasing decisions, while the remainder is influenced by other factors not examined in this study.